Aplikasi Antrian pada SAMSAT di Kota Palopo Berbasis Android - Kirana Kirana; Ahmad Ali Hakam Dani; Rinto Suppa (Dewantara Journal of Technology, 2022)
The purpose of this research is to design and create a Queue Application at the Palopo Samsat Office on Android that is easy to use to process queue data sent by users and provide solutions for the Palopo City Samsat Office to make it easier for people to queue without having to wait at the Palopo Samsat Office and can be accessed using android in taking queues and checking vehicle taxes. The research method used in this research is the waterfall method. Data collection methods in this study are data documentation, data collection, problem identification, observation, and literature study. The application is made using the Unified Modeling Language (UML) development method which consists of use case diagrams, activity diagrams, entity relationships and sequence diagrams. The software used in designing this information system uses an API with the PHP programming language, XAMPP as a web server, MySQL as a database, Android Studio as an editor and design. This research resulted in two applications, the admin application, the web admin and user consisting of several functions. This application has been tested using the Black Box testing method. With this application, it is hoped that it can help the community and the Samsat to take queue numbers and check vehicle taxes. From the results of testing the system using a Likert scale measurement, it shows a feasibility level of 62.8%. The results of the instrument validity test are valid for each item. The result of the instrument reliability test is 0.989 reliable.